Cloud atlas. - Mitchell, David Stephen, 1969- (Londen : Hodder and Stoughton, 2004)
Six interlocking lives - one amazing adventure. In a narrative that circles the globe and reaches from the 19th century to a post-apocalyptic future, David Michell erases the boundaries of time, genre and language to offer an enthralling vision of humanity's will to power, and where it will lead us.
Keywords: Romans